Platybinthus, a new genus of Lebinthina crickets (Orthoptera, Gryllidae, Eneopterinae) from Maluka, Indonesia - Robillard, Tony; Tan, Ming Kai (European Journal of Taxonomy, 2023)
A new genus of Lebinthina (Orthoptera: Gryllidae: Eneopterinae) is erected based on species from Maluka Islands near northern Sulawesi (Indonesia): Platybinthus gen. nov. This new genus currently consists of three species. Platybinthus punctatus (Brunner von Wattenwyl, 1898) gen. et comb. nov. from Halmahera Island is assigned as the type species. Platybinthus striolatus gen. et comb. nov., also from Halmahera Island, is redescribed. We also describe a new species: Platybinthus sandyi gen. et sp. nov. from Morotai Island.